Student Enthusiasm as a Key Determinant of their Performance - ABDULMUMINI, Baba Alfa; MOHD, Zaini Abd Karim (Journal of Research in Educational Sciences; Vol 7 No 8 (2015): Journal of Research in Educational Sciences, 2015)
This paper investigates students’ enthusiasm and their performance over the programme they were given using 400 observations of new students from faculty of management and social sciences. Using OLS motivation, the results indicate that number of peers positively influence their performance, while change of student programme by university management negatively affect their performance. We therefore recommend a free will option to be given to students to choose any programme of their choice and as well move with peers that will positively impact on their performance.